Business Mathematics - Gossage, Loyce c. (California : south-western publishing co., 1984)
Provides the principles for solving business problems and creates awareness of the importance of business mathematics in personal life.
Includes index.
oif 19/02/19
Loan
Keywords: Business mathematics